Attitudes toward Inclusive Education from a Network Perspective - Tom Jannick Selisko; Eric Klopp; Christine Eckert; Franziska Perels (MDPI AG, 2024)
The present study showcases attitudes toward inclusive education in a new light. It contributes to the ongoing debate regarding the extent of inclusive education and highlights the importance of teachers in a process toward inclusion. Based on a framework that involves the reciprocal relation between models of disability, learning theory, and placement of persons with disabilities, attitudes of student teachers and psychology students from a German university are analyzed and mapped through the application of a network approach. This facilitates visualization and categorization based on their statistical relation. An online questionnaire consisting of established and newly developed scales was answered by (n=) 132 student teachers and (n=) 59 psychology students, resulting in n = 191 participants. The study was publicly promoted, and participants were offered study credentials. Using a Spinglass algorithm to analyze the data, we detected two distinct communities in the network: an Exclusion Community and an Inclusion Community. These are supported by further variables (Empathy, Contact, Authoritarianism, and Social Darwinism). The findings demonstrate an especially firm Exclusion Community, whereas inclusive attitudes appear to be varied.